“SPRIGHTLY AT EIGHTY-TWO”: GROWING OLD IN AMY HERZOG’S PLAYS - Gaidash, A.; Ivanova, Y. (Studia Philologica, 2021)
One of the challenges introduced by the contemporary drama is representation of old characters as protagonists on stage. The article tackles the representations of growing old in Amy Herzog’s plays “After the Revolution” and “4000 Miles” relying on the physical and sentimental markers through the examination of the adaptation of the female character to old age. The authors analyze the dramatis personae through the lens of literary gerontology. Growing old in Herzog’s plays is developed from the perspective of intergenerational relationships in both plays. In “4000 Miles”, nonagenarian Vera and young Leo represent a meaningful synthesis of adolescence and late adulthood. In this drama, old age embodies wisdom for younger generation linking grandchildren and grandparents. “After the Revolution” gives another example of intergenerational bond between octogenarian Vera and her granddaughter Emma. Vera’s intervention into Emma’s family case investigation has a positive impact on relationships between them. In addition, Emma gets on well with another senior representative, Morty, Vera’s admirer. There are no prejudices or stereotypes about old age in their conversations, but only Emma’s support and encouragement to undermine the stereotype that old people cannot be involved into romantic relationships. The ways of ageist stereotypes subversion are presented by the extended description of physical process of growing old; using vocabulary rich of aphorisms and slang words to illustrate the elderly’s wisdom and at the same time awareness of the modern language; portraying the elderly as individuals with a wide range of social activities and occupations; older characters are shown as protagonists of the plays, not only minor characters. Key words: growing old, Amy Herzog, dynamics, aged woman character, self-stereotyping, drama, literary gerontology, markers.